2005
DOI: 10.1038/sj.jcbfm.9600215
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenin 1 Mediates Erythropoietin Enhanced Differentiation of Adult Neural Progenitor Cells

Abstract: Proneuronal basic helix-loop-helix (bHLH) transcription factor, neurogenin 1 (Ngn1), regulates neuronal differentiation during development of the cerebral cortex. Akt mediates proneuronal bHLH protein function to promote neuronal differentiation. Here, we show that recombinant human erythropoietin (rhEPO) significantly increased Akt activity and Ngn1 mRNA levels in neural progenitor cells derived from the subventricular zone (SVZ) of adult rat, which was coincident with increases of neural progenitor cell prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 35 publications
4
39
1
Order By: Relevance
“…Consistent with this, inhibition of Akt activity attenuated leptin- induced cell proliferation. Our results are in agreement with previous reports that PI3K-Akt transduces intracellular signals that control adult hippocampal neural progenitor cell proliferation (55,56). Overexpression of Akt increases cell proliferation, whereas expression of a dominant negative Akt inhibits cell proliferation (55,56).…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with this, inhibition of Akt activity attenuated leptin- induced cell proliferation. Our results are in agreement with previous reports that PI3K-Akt transduces intracellular signals that control adult hippocampal neural progenitor cell proliferation (55,56). Overexpression of Akt increases cell proliferation, whereas expression of a dominant negative Akt inhibits cell proliferation (55,56).…”
Section: Discussionsupporting
confidence: 93%
“…Our results indicated that inhibition of these pathways attenuated NSC proliferation and neuronal differentiation induced by the drug. PI3K⅐Akt and Wnt⅐␤-catenin transduce intracellular signals that control adult hippocampal NSC proliferation and differentiation (77,78). Our results are consistent with the previous finding that valproate enhances NPC proliferation in DG via inhibiting GSK-3␤ by its phosphorylation and increasing the levels of ␤-catenin (28).…”
Section: Discussionsupporting
confidence: 92%
“…Hypoxia induction of EPO in brain persists for up to 24 h or more [40]. In cultures of rat embryonic mesencephalic and adult subventricular zone precursor cells, EPO enhances proliferation and neuronal differentiation [41,42], providing further evidence for potential EPO activity in brain. Recently, comparisons of HIF-1α with its isoform, HIF-2α using siRNA technology suggest that HIF-2a, rather than HIF-1a, is the main regulator of EPO expression during hypoxia [43].…”
Section: Epo Production In Brainmentioning
confidence: 90%